1993
DOI: 10.1063/1.465738
|View full text |Cite
|
Sign up to set email alerts
|

The effect of finite film thickness on the surface segregation in symmetric binary polymer mixtures

Abstract: We report neutron reflectivity and dynamic secondary ion mass spectroscopy measurements of surface segregation from symmetric, isotopic polystyrene blends, spin coated onto oxide covered silicon wafers, as a function of film thickness. The results of this analysis show that the segments of the deuterated polymer always partition to both the air and the substrate interfaces. Furthermore, the surface segregation is affected significantly if the film thicknesses are reduced below -four times the correlation lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 12 publications
7
72
0
Order By: Relevance
“…We note that as film thickness decreases, the excess adsorption of nanoparticles also decreases, while the excess adsorption of polymers segments increases. We would like to note here that an earlier report by Hariharan et al 39 found similar behaviour for polymer-polymer blend films. Their results were interpreted in terms of minimization of the density gradients, created by phase segregation of one component of the blend to the interfaces, due to confinement.…”
supporting
confidence: 81%
“…We note that as film thickness decreases, the excess adsorption of nanoparticles also decreases, while the excess adsorption of polymers segments increases. We would like to note here that an earlier report by Hariharan et al 39 found similar behaviour for polymer-polymer blend films. Their results were interpreted in terms of minimization of the density gradients, created by phase segregation of one component of the blend to the interfaces, due to confinement.…”
supporting
confidence: 81%
“…13,20 The reported values for hPS:dPS are nominally 2.0 × 10 -4 over the range of temperatures employed in this investigation (128-166°C). 10,32 Figure 4 shows a theoretical comparison of dPS segregation using ) 0.0 and ) 2.0 × 10 -4 for N hPS ) N dPS ) 1200 and ∆ p ) 0.01.…”
Section: Resultsmentioning
confidence: 85%
“…13,19,20 Similarly where kT∆ p is the net energetic preference per segment for dPS over hPS at an hPMMA "substrate", and λ 1 is a lattice weighting factor (1/6 for cubic). 18 As shown in eq 3, ∆ p should be proportional to a simple difference in values for dPS/ hPMMA and hPS/hPMMA.…”
Section: Resultsmentioning
confidence: 99%
“…A 50 nm (approximate) hPS sacrificial layer was added to the sample before analysis to avoid pre-equilibrium sputtering at the hPS: dPS surface. For the novel 13 C depth profiling investigation, 13 C-PS, 12 C-PS, and 12 C-PMMA were synthesized using atom transfer radical polymerization (ATRP) with previously outlined conditions [16], and are listed in Table 1. A mixture of 33% ␣,␤- C-PS was cast onto Si (100) that had a 2 nm native oxide (SiO x ) layer to a thickness of 180 nm and annealed at 125°C for 24 h. A second set of samples was prepared to evaluate the effects of isotopic labeling at the PS/PMMA interface.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Unfortunately, it can introduce changes in the properties being measured. For instance, it has been established that deuterium substitution can affect polymer/polymer phase behavior, with reported changes in both bulk [8 -10] and surface interactions [11,12], and deuterium substitution has even been shown to alter polymer-solvent phase behavior [13]. More recently, it has been found that deuterium substitution can have a profound effect on the properties of a polymer/polymer heterogeneous interface, with the observation of diffusion-controlled segregation of deuterium labeled polystyrene (dPS) to an hPS:dPS/ poly(methyl methacrylate) (hPMMA) interface [14].…”
mentioning
confidence: 99%